Heartburn treatment in primary care: randomised, double blind study for 8 weeks. Issue 7209 (28th August 1999) - Hatlebakk, Jan G; Hyggen, Arild; Madsen, Per H; Walle, Per O; Schulz, Tom; Mowinckel, Petter; Bernklev, Tomm; Berstad, Arnold
Abstract: Objective: To compare the effects and tolerability of omeprazole and cisapride with that of placebo for control of heartburn in primary care patients. Design: Randomised, double blind, placebo controlled study Setting: 65 primary care practices in Norway Participants: 483 untreated patients with complaints of heartburn ≥3 days a week, with at most grade 1 reflux oesophagitis Interventions: Omeprazole 20 mg once daily, cisapride 20 mg twice daily, or placebo for 8 weeks Main outcome measures: Adequate control of heartburn, defined as ≥1 day of the past 7 days with no more than mild heartburn, after 4 weeks of treatment. Results: In the all patients treated analysis, adequate control of heartburn was achieved in 71% of patients taking omeprazole, 22% taking cisapride, and 18% taking placebo after 4 weeks of treatment (omeprazole v cisapride and placebo, P<0.0001; cisapride v placebo, non-significant). Results were comparable in patients with or without reflux oesophagitis. In patients treated with omeprazole only, symptom control was achieved significantly more often in patients positive for Helicobacter pylori . Antacid use was 2-3 times greater in patients taking cisapride or placebo than in those taking omeprazole. Relief of non-reflux symptoms did not significantly differ between the three groups. Significantly more patients taking cisapride reported adverse events than those taking omeprazole or placebo. Conclusions: Omeprazole 20 mg once daily was highly effective in relieving heartburn whereas cisapride 20 mg twice daily was not significantly more effective than placebo.